Intraparenchymal Epididymal Cyst (IEC) 4 cm in Diameter in a 15-Year Old Male Patient; a Case Report and Review of the Literature - Dimitrios Patoulias; Maria Kalogirou; Ioannis Patoulias (Acta Medica, 2017)
ntraparenchymal epididymal cysts (IECs) are benign cystic formations of the epididymis of unknown pathogenesis, which typically appear in adolescence or adulthood. In patients older than 14 years old their prevalence is doubled. After systematic and thorough research of the current literature, we did not find another case report of intraparenchymal epididymal cyst with similar dimensions. The male patient, 15 years old, visited our outpatient department complaining of pain in the right hemiscrotum. Diagnosis of IEC was confirmed after the conduction of ultrasound examination. Patient underwent surgical exploration of the right hemiscrotum. Resection of the IEC followed. Postoperative course was uneventful, with recession of the symptoms. In our opinion, IECs should be surgically removed, either when they are symptomatic or when they are asymptomatic, but of a diameter greater than 1 cm and without regression tendency.